Resin composition and molded article

The resin composition, comprising a styrene resin with a diene component and calcium carbonate-based inorganic filler, addresses the brittleness and moldability issues of conventional compositions by achieving enhanced tensile properties and environmental sustainability.

JP7657293B2Active Publication Date: 2025-04-04DENKA CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023516363
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-20
Filing Date
2022-03-24
Publication Date
2025-04-04
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

Conventional resin compositions containing polystyrene resin and high amounts of inorganic fillers face challenges in achieving sufficient tensile modulus, tensile elongation at break, and moldability due to brittleness and reduced flowability.

Method used

A resin composition combining a styrene resin containing a diene component with an inorganic filler containing calcium carbonate, where the inorganic filler content is 50% by mass or more, achieving a tensile elastic modulus of 1,000 to 3,000 MPa and a tensile elongation at break of 5% or more.

Benefits of technology

The resin composition achieves excellent moldability and balanced tensile properties, even with a high content of inorganic filler, while reducing the environmental impact by minimizing the styrene-based resin content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657293000001
    Figure 0007657293000001
  • Figure 0007657293000002
    Figure 0007657293000002
  • Figure 0007657293000003
    Figure 0007657293000003
Patent Text Reader

Abstract

[Problem] To provide: a resin composition that contains a small amount of a styrene-based resin, that has a small environmental impact, that has good moldability, and that can be used to obtain a molded article having excellent tensile elastic modulus and tensile elongation at break; and a molded article of the resin composition. [Solution] A resin composition comprising: an inorganic filler that includes calcium carbonate; and a styrene-based resin containing a diene component, wherein the contained amount of the inorganic filler is at least 50 mass% with respect to the total mass of the resin composition, and the tensile elastic modulus of the resin composition is 1,000-3,000 MPa and the tensile elongation at break of the resin composition is at least 5% as measured in accordance with ASTM-D638.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article thereof. More specifically, the present invention relates to a resin composition having a low content of styrene-based resin and thus having a low environmental impact, and a molded article thereof. [Background technology]

[0002] In general, resin products used in home appliances, automobile interior materials, toys, etc. are molded by injection molding or the like. Polystyrene resin is a representative thermoplastic resin, and since it has excellent transparency, moldability, and is inexpensive, it is widely used in the above-mentioned applications as a thermoplastic resin for injection molding. Among these applications, in fields where physical properties such as heat resistance and rigidity are required, it is known to blend inorganic fillers such as calcium carbonate, talc, and zeolite into polystyrene resin (for example, Patent Document 1, etc.). However, since polystyrene resin is highly brittle, molded products obtained from resin compositions containing a large amount of inorganic fillers have a problem of insufficient tensile modulus of elasticity and tensile elongation at break. In addition, such resin compositions also have a reduced fluidity required for injection molding.

[0003] In recent years, environmental issues such as global warming have come to be emphasized, and it is desired to reduce the amount of resin materials derived from fossil resources such as petroleum. In the field of injection molded products, resin products with a low ratio of thermoplastic resin derived from fossil resources are also desired, and a method of increasing the blending amount of additives such as inorganic fillers not derived from fossil resources (Patent Document 2) and a resin composition blended with a material derived from biomass (Patent Document 3) have been studied. However, as mentioned above, in a resin composition containing polystyrene resin, increasing the blending amount of inorganic fillers makes the resin brittle, lowering the tensile modulus of elasticity and tensile elongation at break of the molded product, and also worsening moldability. The same is true when biomass materials are blended, and if the blending rate of the biomass materials is increased, it is not possible to satisfy the various physical properties required for injection molded products. Therefore, with conventional technology, it is difficult to obtain a resin composition with a low environmental load in which the ratio of styrene-based resin is reduced to 50 mass% or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-267350 [Patent Document 2] JP 2019-077148 A [Patent Document 3] JP 2018-119048 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in consideration of the above circumstances, and has an object to provide a resin composition which has a low content of styrene-based resin and imposes a low burden on the environment, has good moldability, and can give a molded article having excellent tensile modulus and tensile elongation at break, and a molded article thereof. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors conducted intensive research into the above-mentioned problems and found that a resin composition that can solve all of the above-mentioned problems can be obtained by combining a styrene-based resin containing a diene component with an inorganic filler containing calcium carbonate, thereby completing the present invention. That is, the present invention has the following aspects. [1] A resin composition comprising an inorganic filler containing calcium carbonate and a styrene-based resin containing a diene component, the content of the inorganic filler being 50 mass% or more based on the total mass of the resin composition, and the resin composition having a tensile modulus of elasticity of 1,000 to 3,000 MPa and a tensile elongation at break of 5% or more, measured in accordance with ASTM-D638. [2] The resin composition according to [1], wherein the inorganic filler contains eggshell powder. [3] The resin composition according to [2], wherein the eggshell powder has an average particle size of 3 to 50 μm. [4] The resin composition according to any one of [1] to [3], wherein the styrene-based resin comprises a polystyrene resin and a styrene-based thermoplastic elastomer. [5] The resin composition according to [4], wherein the polystyrene resin comprises at least one resin selected from general-purpose polystyrene and high-impact polystyrene. [6] The resin composition according to [4] or [5], wherein the styrene-based thermoplastic elastomer contains a styrene-butadiene copolymer. [7] The resin composition according to any one of [1] to [6], wherein the content of the diene component relative to the total mass of the resin composition is 3 to 15 mass%. [8] The resin composition according to any one of [1] to [7], wherein the MFR (200°C, 5 kg load) of the resin composition is 1.5 g / 10 min or more. [9] The resin composition according to any one of [1] to [8], which is for injection molding.

[10] A molded article comprising the resin composition according to any one of [1] to [9]. Effect of the Invention

[0007] According to the present invention, it is possible to provide a resin composition which has a low content of styrene-based resin and imposes a low burden on the environment, has good moldability, and can give a molded article which is excellent in tensile modulus and tensile elongation at break, and a molded article made from the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below, but the present invention is not limited to the following embodiments. In this specification, the symbol "~" means "at least one or less than one." In other words, "3 to 50" means "at least one or more than 3 and at most 50." [Resin composition] The resin composition according to the present invention is a resin composition comprising an inorganic filler containing calcium carbonate and a styrene-based resin containing a diene component, the content of the inorganic filler being 50% by mass or more relative to the total mass of the resin composition, and the tensile modulus of elasticity is 1,000 to 3,000 MPa and the tensile elongation at break is 5% or more, as measured according to ASTM-D638. The resin composition according to the present invention can reduce the content of the styrene-based resin while achieving moldability suitable for injection molding. Furthermore, a molded product excellent in tensile modulus of elasticity and tensile elongation at break can be provided.

[0009] The resin composition according to the present invention has a tensile modulus of elasticity of 1,000 to 3,000 MPa measured according to ASTM-D638. In this specification, the terms "tensile modulus of elasticity of the resin composition" and "tensile elongation at break of the resin composition" refer to the tensile modulus of elasticity and the tensile elongation at break measured using a test piece of the resin composition prepared according to ASTM-D638. If the tensile modulus of elasticity of the test piece is 1,000 to 3,000 MPa, the tensile modulus of the molded article obtained from the resin composition is also good, and a molded article having an excellent balance between strength and flexibility can be obtained. The tensile modulus may be 1,000 to 2,600 MPa, 1,000 to 1,900 MPa, or 1,200 to 1,800 MPa. The tensile modulus is a value measured in accordance with ASTM-D638, and specifically means a value measured under the following conditions. (Method for measuring tensile modulus) The resin composition is molded into a plate having a thickness of 0.40 mm, and then cut into a No. 1 dumbbell shape to prepare 10 measurement samples. The tensile modulus of the measurement samples is then measured using an autograph in accordance with ASTM-D638 under conditions of a measurement temperature of 23°C and a humidity of 50% at a tensile speed of 5 mm / min. The tensile modulus of all the measurement samples is measured, and the average value is regarded as the tensile modulus of the resin composition.

[0010] Moreover, the resin composition according to the present invention has a tensile breaking elongation of 5% or more as measured according to ASTM-D638. If the resin composition has a tensile breaking elongation of 5% or more, the tensile breaking elongation of the obtained molded article is also good, and a molded article having an excellent balance between strength and flexibility can be obtained. The tensile breaking elongation may be 10% or more, or may be 15% or more. From the viewpoint of moldability, the tensile breaking elongation may be 5 to 100%. The tensile breaking elongation is a value measured according to ASTM-D638, and specifically means a value measured under the following conditions. (Method of measuring tensile elongation at break) The resin composition is molded into a plate having a thickness of 0.40 mm, and then cut into a No. 1 dumbbell shape to prepare 10 measurement samples. The tensile elongation at break of the measurement samples is then measured at a tensile speed of 5 mm / min using an autograph in accordance with ASTM-D638 under conditions of a measurement temperature of 23°C and a humidity of 50%. The tensile elongation at break of all the measurement samples is measured, and the average value is taken as the tensile elongation at break of the resin composition.

[0011] The melt flow rate (MFR) of the resin composition according to the present invention is preferably 1.5 g / 10 min or more, more preferably 2.0 g / 10 min or more, at 200° C. and 5 kg load, evaluated according to the standard of JIS K 7260. If the MFR (200° C., 5 kg load) of the resin composition is 1.5 g / 10 min or more, the flowability is likely to be good, and the moldability is likely to be good.

[0012] <Inorganic filler containing calcium carbonate> The resin composition according to the present invention contains 50% by mass or more of an inorganic filler containing calcium carbonate, based on the total mass of the resin composition. Since the resin composition according to the present invention contains a styrene-based resin containing a diene component as a thermoplastic resin component, even if the resin composition contains 50% by mass or more of an inorganic filler, the moldability is not deteriorated. In addition, a molded product excellent in tensile modulus and tensile elongation at break can be provided. The proportion of the inorganic filler is 50% by mass or more, preferably 50 to 70% by mass, more preferably 50 to 60% by mass, based on the total mass of the resin composition.

[0013] The inorganic filler contains calcium carbonate. The proportion of calcium carbonate in the inorganic filler is preferably 90% by mass or more, more preferably 93 to 100% by mass, and even more preferably 95 to 100% by mass, based on the total mass of the inorganic filler. When the proportion of calcium carbonate in the inorganic filler is within the above range, a molded product having excellent tensile modulus and tensile elongation at break is easily obtained.

[0014] The inorganic filler may contain a filler other than calcium carbonate (other filler). Examples of the other filler include talc. The other filler may be contained alone or in combination of two or more. The other filler may be contained in an amount of less than 10% by mass based on the total mass of the inorganic filler.

[0015] In one embodiment, the inorganic filler containing calcium carbonate according to the present invention may be a biomineral. "Biomineral" refers to minerals produced by living organisms, and examples thereof include pearls, shells, eggshells, bones, and exoskeletons of crustaceans. When using "biomineral" as the inorganic filler according to the present invention, it is preferable to use eggshell powder or shell powder. These eggshell powder and shell powder are inorganic fillers mainly composed of calcium carbonate. In addition, from the viewpoint of further reducing the burden on the environment, it is preferable that the eggshell powder and shell powder are powders derived from food waste. Among these, it is more preferable to include eggshell powder. In addition to processing residues generated during the production and cooking of food, "derived from food waste" may be materials derived from food waste such as unsold or leftover food generated during the distribution process or consumption stage of food.

[0016] As the eggshell powder, one made from chicken eggshells is preferred. More than 200,000 tons of chicken eggshells are disposed of annually, and it is desired to make effective use of them. In addition, chicken eggshells generally contain 95% by mass or more of calcium carbonate. The resin composition according to the present invention preferably contains chicken eggshell powder as an inorganic filler containing calcium carbonate. In one embodiment, the inorganic filler may be eggshell powder alone or a mixture of eggshell powder and commercially available calcium carbonate. Here, "commercial calcium carbonate" means a filler that is chemically produced using a raw material that is not derived from a biomineral, such as limestone, as a raw material. When a mixture of eggshell powder and commercially available calcium carbonate is used as the inorganic filler, the ratio of eggshell powder in the mixture is preferably 60 to 100% by mass, more preferably 70 to 100% by mass, from the viewpoint of utilizing natural waste materials. In addition, the mixture may contain other fillers described above other than calcium carbonate.

[0017] When eggshell powder is blended as an inorganic filler, the viscosity of the resin composition is likely to increase if finer powder is used, and the flowability during molding may decrease. In addition, the dispersibility of the eggshell powder in the resin composition is likely to decrease. On the other hand, if the average particle size is too large, it is difficult to obtain a molded product with the desired strength and flexibility. From these viewpoints, the average particle size of the eggshell powder is preferably 3 to 50 μm, more preferably 3 to 40 μm, and even more preferably 4 to 30 μm. In particular, it is preferable that the upper limit of the average particle size of the eggshell powder is 50 μm or less. When eggshell powder having an average particle size larger than 50 μm is blended, the resin is likely to break, and it is difficult to obtain the desired elongation. The average particle size of the eggshell powder means a value measured by a particle size distribution measuring device according to the "sieving method". The specific gravity of the eggshell powder is preferably 2.0 to 3.0, more preferably 2.0 to 2.8, and particularly preferably 2.3 to 2.7.

[0018] The above-mentioned eggshell powder can be prepared by a conventionally known manufacturing method. That is, eggshells are pulverized by a conventional method, and then classified to obtain eggshell powder having a desired average particle size. Specifically, after removing the eggshell membrane from the eggshell, the eggshell is dried. Then, the eggshell is pulverized with a pulverizer or the like to obtain eggshell powder. Then, the eggshell powder can be obtained by classifying the resulting product using a sieve with an appropriate mesh size. In addition, commercially available eggshell powder can also be used, such as GT-26 (product name) manufactured by Green Techno 21 Co., Ltd. and Calhope (registered trademark) (product name) manufactured by Kewpie Egg Co., Ltd.

[0019] When the inorganic filler according to the present invention is eggshell powder, the content of the eggshell powder in the resin composition is 50 mass% or more, preferably 50 to 70 mass%, and more preferably 50 to 65 mass%, relative to the total mass of the resin composition.

[0020] <Styrene-based resin containing diene component> The resin composition according to the present invention contains a styrene-based resin containing a diene component. By containing a styrene-based resin containing a diene component, even if the aforementioned inorganic filler is blended in an amount of 50 mass% or more, the resin composition does not become brittle and has good moldability. In addition, moldability excellent in tensile modulus and tensile elongation at break can be obtained. Here, "containing a diene component" means containing a styrene-based resin containing a monomer unit derived from a conjugated diene, containing a monomer of a conjugated diene, containing a rubbery polymer of a conjugated diene rubber or a copolymer containing a conjugated diene, or containing one or more of these. In addition, "styrene-based resin" means containing one or more polymers containing a monomer unit derived from an aromatic vinyl compound. The "styrene-based resin containing a diene component" according to the present invention may be composed of one type of polymer containing a monomer unit derived from a conjugated diene and a monomer unit derived from an aromatic vinyl compound, or may be a mixture of multiple polymers as described below. Hereinafter, the styrene-based resin containing a diene component may be simply referred to as a "styrene-based resin".

[0021] The proportion of the diene component in the resin composition is preferably 3 to 15 mass%, more preferably 3 to 14 mass%, and particularly preferably 4 to 12 mass%, based on the total mass of the resin composition. If the proportion of the diene component in the resin composition is within the above range, even if 50 mass% or more of an inorganic filler is blended, the moldability is likely to be good. In addition, the tensile modulus and tensile elongation at break of the molded article are unlikely to decrease. The proportion of the diene component in the resin composition may be a value calculated from the blending amount of the styrene-based resin, or may be a value measured by the following method. As a method for calculating from the amount of the styrene-based resin, for example, when a styrene-based resin whose amount of diene component is known in advance is used, the calculation can be made from [(amount of diene component in the styrene-based resin (% by mass)) × (amount of the styrene-based resin (% by mass))] / total mass of the resin composition (100% by mass). The method for measuring the diene content in the resin composition may be, for example, a method in which the diene content in the resin composition is measured by potentiometric titration using iodine monochloride, potassium iodide and sodium thiosulfate standard solutions, and the diene content is taken as the ratio of the diene content in the resin composition. A specific measuring method may be, for example, the method described in "New Edition Polymer Analysis Handbook", edited by the Polymer Analysis Research Roundtable of the Japan Analytical Chemistry Society, Kinokuniya Shoten (1995 edition), p. 659 (3) Rubber Content.

[0022] The ratio of the diene component in the styrene-based resin according to the present invention is preferably 5 to 40% by mass, more preferably 6 to 30% by mass, and particularly preferably 8 to 28% by mass, based on the total mass of the styrene-based resin. If the ratio of the diene component is within the above range, the ratio of the diene component in the resin composition can be easily adjusted to the above preferred range. In addition, even if the content of the styrene-based resin in the resin composition is reduced, the moldability is unlikely to deteriorate. In addition, the tensile modulus and tensile elongation at break of the obtained molded product are unlikely to decrease. The ratio of the diene component in the styrene-based resin can be determined by the same method as the calculation method and measurement method of the diene component in the resin composition described above.

[0023] The proportion of the styrene-based resin containing a diene component in the resin composition is preferably 50% by mass or less based on the total mass of the resin composition. From the viewpoint of the rigidity of the molded product, the styrene-based resin is preferably contained in an amount of 30% by mass or more. That is, the proportion of the styrene-based resin in the resin composition is more preferably 35 to 50% by mass, and further preferably 40 to 50% by mass.

[0024] The styrene-based resin according to the present invention may be a mixture of a plurality of resins. When the styrene-based resin is a mixture of a plurality of resins, it may contain a polystyrene resin and a styrene-based thermoplastic elastomer.

[0025] (Polystyrene resin) The polystyrene resin according to the present invention means a polymer of an aromatic vinyl compound, a copolymer of an aromatic vinyl compound and a compound copolymerizable with an aromatic vinyl compound, or a polymer obtained by polymerizing these in the presence of a rubber polymer. Examples of aromatic vinyl compounds include styrene, α-methylstyrene, p-methylstyrene, o-methylstyrene, m-methylstyrene, ethylstyrene, and pt-butylstyrene. These aromatic vinyl compounds may be used alone or in combination of two or more. Among these, it is preferable to use styrene.

[0026] Examples of compounds copolymerizable with aromatic vinyl compounds include methacrylic acid esters such as methyl methacrylate and ethyl methacrylate; unsaturated nitrile compounds such as acrylonitrile and methacrylonitrile; and acid anhydrides such as maleic anhydride. The mass proportion of the copolymerizable compound is preferably 20 mass % or less, and more preferably 15 mass % or less, based on the total amount (100 mass %) of the aromatic vinyl compound and the copolymerizable compound.

[0027] Examples of rubbery polymers include conjugated diene rubber, copolymers of conjugated dienes and aromatic vinyl compounds, ethylene-propylene copolymer rubbers, etc. More specifically, examples of rubbery polymers include polybutadiene, styrene-butadiene random copolymers, styrene-butadiene block copolymers, and polymers obtained by hydrogenating a part or all of these.

[0028] The weight average molecular weight (Mw) of the polystyrene resin is preferably 10,000 to 500,000, and more preferably 100,000 to 300,000. If the Mw of the polystyrene resin is within the above range, the fluidity is likely to be good. The Mw of the polystyrene resin refers to a value calculated in terms of polystyrene by GPC (gel permeation chromatography).

[0029] The polystyrene resin may be high impact polystyrene (hereinafter, sometimes referred to as "HIPS") or general purpose polystyrene (homopolystyrene, hereinafter, sometimes referred to as "GPPS"). In one embodiment, the polystyrene resin preferably contains at least one resin selected from HIPS and GPPS. Note that the polystyrene resin does not include the styrene-based thermoplastic elastomer described below.

[0030] When the styrene resin contains a polystyrene resin and a styrene thermoplastic elastomer, the proportion of the polystyrene resin relative to the total amount (100% by mass) of the polystyrene resin and the styrene thermoplastic elastomer is preferably 20 to 95% by mass, more preferably 40 to 80% by mass. If the proportion of the polystyrene resin relative to the total amount is within the above range, the proportion of the diene component of the styrene resin is easy to adjust. In addition, the proportion of the polystyrene resin in the resin composition is preferably 10 to 40% by mass, more preferably 20 to 32% by mass, relative to the total mass of the resin composition.

[0031] (styrene-based thermoplastic elastomer) The styrene-based thermoplastic elastomer according to the present invention is a block copolymer of an aromatic vinyl compound and a conjugated diene, and a hydrogenated product thereof. Examples of the aromatic vinyl compound include the same compounds as those for the polystyrene resin described above, and styrene is more preferred. Examples of the styrene-based thermoplastic elastomer according to the present invention include block copolymers such as styrene-butadiene (SB), styrene-isoprene (SI), styrene-butadiene-butylene (SBB), styrene-butadiene-isoprene (SBI), styrene-butadiene-styrene (SBS), styrene-butadiene-butylene-styrene (SBBS), styrene-isoprene-styrene (SIS), and styrene-butadiene-isoprene-styrene (SBIS), as well as block copolymers obtained by hydrogenating these. These may be used alone or in combination of two or more. Of these, the styrene-based thermoplastic elastomer preferably includes a styrene-butadiene copolymer.

[0032] The weight average molecular weight (Mw) of the styrene-based thermoplastic elastomer is preferably 100,000 to 200,000, more preferably 120,000 to 180,000. If the Mw of the styrene-based thermoplastic elastomer is within the above range, the compatibility with the polystyrene resin tends to be good. The Mw of the styrene-based thermoplastic elastomer is measured by GPC under the same conditions as those of the polystyrene resin described above.

[0033] The ratio of the diene component in the styrene-based thermoplastic elastomer is preferably 10 to 80% by mass, more preferably 13 to 70% by mass, and even more preferably 15 to 60% by mass, based on the total mass of the styrene-based thermoplastic elastomer, from the viewpoint of easily adjusting the tensile modulus to a moldable range. The diene component in the styrene-based thermoplastic elastomer may be a value calculated from the amount of the conjugated diene charged, or may be a value measured by the above-mentioned method. The method for measuring the diene component of the styrene-based thermoplastic elastomer may be the same as the method for measuring the diene content in the resin composition described above.

[0034] When the styrene-based resin contains a polystyrene resin and a styrene-based thermoplastic elastomer, the proportion of the styrene-based thermoplastic elastomer relative to the total amount (100% by mass) of the polystyrene resin and the styrene-based thermoplastic elastomer is preferably 10 to 70% by mass, more preferably 20 to 60% by mass. If the proportion of the styrene-based thermoplastic elastomer relative to the total amount is within the above range, the proportion of the diene component in the styrene-based resin is easily adjusted. In addition, the proportion of the styrene-based thermoplastic elastomer in the resin composition is preferably 5 to 40% by mass, more preferably 8 to 30% by mass, relative to the total mass of the resin composition. In one embodiment, the styrene resin may be composed only of a styrene thermoplastic elastomer. When the styrene resin is composed only of a styrene thermoplastic elastomer, it is preferable to adjust the diene component of the styrene thermoplastic elastomer so that the amount of the diene component in the resin composition is in the range of 3 to 15 mass%.

[0035] As described above, the resin composition according to the present invention has a tensile elongation at break of 5% or more and a tensile modulus of elasticity of 1,000 to 3,000 MPa, even though the resin composition contains 50% or more by mass of inorganic filler relative to the total mass of the resin composition. In general, when the proportion of inorganic filler is increased and the proportion of resin component is further decreased, the resin easily breaks and sufficient elongation cannot be obtained. That is, the molded product is hard and brittle. The present inventors have found that by blending a styrene-based resin containing a certain amount of diene component, sufficient elongation can be obtained even with a small amount of resin, and the modulus of elasticity can be suppressed from becoming too high. Furthermore, it has also been found that by combining a polystyrene resin such as GPPS or HIPS with a styrene-based thermoplastic elastomer, the balance between the modulus of elasticity and elongation is improved even when the proportion of the resin component in the resin composition is 50% by mass or less, and a molded product having a better balance between flexibility and strength can be easily obtained.

[0036] The resin composition according to the present invention may contain a thermoplastic resin (other thermoplastic resin) other than the styrene-based resin. However, from the viewpoint of obtaining a resin composition having a low resin content, it is preferable that the resin composition does not contain other thermoplastic resins.

[0037] The resin composition according to the present invention may contain, as necessary, other additives such as ultraviolet absorbers, light stabilizers, antioxidants, lubricants, plasticizers, colorants, antistatic agents, flame retardants, and mineral oils, and reinforcing fibers such as glass fibers, carbon fibers, and aramid fibers. These may be used alone or in combination of two or more.

[0038] Examples of the ultraviolet absorber include 2-(5'-methyl-2'-hydroxyphenyl)benzotriazole, 2-(5'-t-butyl-2'-hydroxyphenyl)benzotriazole, 2-[2'-hydroxy-3',5'-bis(α,α-dimethylbenzyl)phenyl]benzotriazole, 2-(3',5'-di-t-butyl-2'-hydroxyphenyl)benzotriazole, 2-(3'-t-butyl-5'-methyl-2'-hydroxyphenyl)-5-chlorobenzotriazole, 2-(3',5'-di-t-butyl-2'-hydroxyphenyl)benzotriazole, 2-(3',5'-di-t-amyl-2'-hydroxyphenyl)benzotriazole, 2-[3'-(3”,4”,5”,6”-tetrahydrophthalimidomethyl)-5'-methyl-2'-hydroxyphenyl]benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole-2-yl)phenol] and other benzotriazole-based ultraviolet absorbers; 2-ethoxy-2'-ethyl oxalic acid bisanilide, 2-ethoxy-5-t-butyl oxalic acid anilide ultraviolet absorbers such as 2-ethyl-2'-ethyl oxalic acid bisanilide and 2-ethoxy-4'-isodecylphenyl oxalic acid bisanilide; 2-hydroxy-4-n-octoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone; Examples of the ultraviolet absorbing agent include benzophenone-based ultraviolet absorbers; salicylic acid-based ultraviolet absorbers such as phenyl salicylate, pt-butylphenyl salicylate, and p-octylphenyl salicylate; cyanoacrylate-based ultraviolet absorbers such as 2-ethylhexyl-2-cyano-3,3'-diphenylacrylate and ethyl-2-cyano-3,3'-diphenylacrylate; and titanium oxide-based ultraviolet stabilizers such as rutile titanium oxide, anatase titanium oxide, alumina, silica, titanium oxide treated with a surface treatment agent such as a silane coupling agent or a titanium-based coupling agent.These may be used alone or in combination of two or more.

[0039] Examples of light stabilizers include bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, dimethyl succinate·1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine polycondensate, and poly[[6,(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl] [(2,2,6,6-tetramethyl-4-piperidyl)imino]-hexamethylene-[(2,2,6,6-tetramethyl-4-piperidyl)imino]], 1-[2-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy]ethyl]-4-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy]-2,2,6,6-tetramethylpiperidine, etc. These may be used alone or in combination of two or more.

[0040] Examples of the antioxidant include triethylene glycol bis[3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, pentaerythrityl tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl phenol-based antioxidants such as 2,2-thiobis(4-methyl-6-t-butylphenol) and 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene; ditridecyl-3,3'-thiodipropionate, dilauryl-3,3'-thiodipropionate, ditetradecyl-3,3'-thiodipropionate, distearyl-3,3' -thiodipropionate, dioctyl-3,3'-thiodipropionate and other sulfur-based antioxidants; trisnonylphenyl phosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl-di-tridecyl)phosphite, (tridecyl)pentaerythritol diphosphite, bis(octadecyl)pentaerythritol diphosphite, bis(di-t-butylphenyl)pentaerythritol diphosphite, bis Examples of the phosphorus-based antioxidants include (di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, dinonylphenyl octyl phosphonite, tetrakis(2,4-di-t-butylphenyl)1,4-phenylene diphosphonite, tetrakis(2,4-di-t-butylphenyl)4,4'-biphenylene diphosphonite, and 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene. These may be used alone or in combination of two or more.

[0041] [Method of producing resin composition] The resin composition according to the present invention can be produced by melt-kneading an inorganic filler containing calcium carbonate, a styrene-based resin containing a diene component, and other components as necessary. Specifically, a styrene-based resin containing a diene component (more preferably, a polystyrene resin and a styrene-based thermoplastic elastomer) and an inorganic filler containing calcium carbonate (more preferably, eggshell powder) are each fed into a twin-screw extruder, melt-kneaded at a temperature of 200 to 250°C, and then extruded in a strand shape to prepare a pellet-shaped resin composition. The resin composition according to the present invention contains an inorganic filler containing calcium carbonate in an amount of 50% by mass or more based on the total mass of the resin composition, and therefore has a low content of resin material.

[0042] [Application] As described above, the resin composition according to the present invention has good moldability even though it contains 50% by mass of an inorganic filler. Therefore, it is suitable as a resin composition for injection molding. However, the use of the resin composition according to the present invention is not limited to injection molding.

[0043] [Molded products] The molded article according to the present invention contains the resin composition described above. It is preferably obtained by injection molding the resin composition according to the present invention. The molded article according to the present invention is excellent in tensile modulus and tensile elongation at break. In addition, the molded article according to the present invention has a resin material ratio of 50 mass % or less, so that it has a low environmental impact. The molded article according to the present invention can be used for stationery, furniture, building materials, tableware, containers, gardening materials, toys, etc.

[0044] More preferred embodiments of the resin composition according to the present invention are as follows. <1> A resin composition comprising an inorganic filler containing calcium carbonate, and a styrene-based resin containing a diene component, the styrene-based resin being composed of a polystyrene resin and a styrene-based thermoplastic elastomer, wherein the proportion of the inorganic filler is 50 to 60 mass%, the proportion of the styrene-based resin is 40 to 50 mass%, and the proportion of the diene component is 3 to 15 mass%, relative to the total mass of the resin composition, and the resin composition has a tensile modulus of elasticity of 1,000 to 3,000 MPa and a tensile elongation at break of 5% or more, as measured in accordance with ASTM-D638. <2> The inorganic filler comprises at least one biomineral-derived powder selected from eggshell powder and seashell powder; <1> The resin composition according to claim 1. <3> The average particle size of the powder derived from the biomineral is 3 to 50 μm. <2> The resin composition according to claim 1. <4> The polystyrene resin comprises at least one resin selected from HIPS and GPPS; <1> from <3> The resin composition according to any one of the preceding claims. <5> <1> from <4> An injection-molded article comprising the resin composition according to any one of claims 1 to 5. EXAMPLES

[0045] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.

[0046] [Preparation of inorganic filler 1 containing calcium carbonate] As inorganic filler 1 containing calcium carbonate, eggshell powder was prepared. First, chicken eggshells were washed with water and then placed in a hot air dryer for drying. The dried eggshells were placed in an agitation separation tank and agitated while being sprayed with high pressure water to separate and remove the egg membrane inside the eggshell. The eggshells from which the egg membrane had been separated and removed were then placed back in the hot air dryer and dried at 90-120°C for 6 hours. The dried eggshells were pulverized using a grinder to obtain eggshell powder. The specific gravity of the obtained eggshell powder was measured using a specific gravity meter (Shimadzu Corporation, product name "Dry-type automatic density meter Accupic II 1340") and was found to be 2.6 g / cm. 3It was. Further, the obtained powder was classified to obtain an inorganic filler 1 (eggshell powder) with an average particle diameter of 10 μm.

[0047] [Preparation of Inorganic Fillers 2 to 4 Containing Calcium Carbonate] In the same manner as for inorganic filler 1, three types of eggshell powders with different average particle diameters were prepared and used as inorganic fillers 2 to 4. Table 1 shows the average particle diameter and specific gravity of each inorganic filler.

[0048]

Table 1

[0049] [Preparation of Polystyrene Resin 1] To a polymerization kettle with an internal volume of 200 L, 70.4 kg of pure water and 300 g of tricalcium phosphate were added and stirred. Then, 80.0 kg of styrene and 267.2 g of benzoyl peroxide were added, sealed, and reacted at 100 °C for 6 hours. After the reaction was completed, the reaction product was cooled, neutralized, dehydrated, and dried to obtain a homopolymer of polystyrene (GPPS). When the Mw of the obtained GPPS was measured using GPC under the following conditions, it was 167,000. <Measurement Conditions of GPC> Apparatus: Manufactured by Shodex Co., Ltd., product name "Shodex SYSTEM-21" Column: PLgel MIXED-B Measurement temperature: 40 °C Solvent: Tetrahydrofuran Flow rate: 1.0 mL / min Detection method: RI Sample concentration: 0.2 mass% Injection volume: 100 μL Calibration curve: Standard polystyrene (manufactured by Polymer Laboratories)

[0050] [Preparation of Polystyrene Resin 2] Low-cis polybutadiene rubber (manufactured by Asahi Kasei Corporation, product name "Diene 55AS") was used as the rubber polymer, and this rubber polymer (5.3% by mass relative to the total mass of the polymerization raw materials) and styrene were dissolved in ethylbenzene (5% by mass relative to the total mass of the polymerization raw materials) as a solvent to prepare the polymerization raw materials. In addition, 0.1 parts by mass of an antioxidant for rubber polymers (manufactured by Nippon Ciba-Geigy Co., Ltd., product name "Irganox (registered trademark) 1076") was added. This polymerization raw material was supplied at 12.5 kg / hr to a 14 L jacketed reactor (R-01) equipped with an anchor-shaped stirring blade with a blade diameter of 0.285 m. The reaction temperature was 140 ° C., and the rotation speed was 2.17 sec. -1 The mixture was stirred at 100° C. for polymerization to obtain a polymer liquid. The polymer percentage of the obtained polymer liquid was 25%. This polymer liquid was introduced into two 21 L jacketed plug-flow reactors arranged in series. In the first plug-flow reactor (R-02), the jacket temperature was adjusted so that the reaction temperature was 120 to 140° C. in the direction of the flow of the polymer liquid. In the second plug-flow reactor (R-03), the jacket temperature was adjusted so that the reaction temperature had a gradient of 130 to 160° C. in the direction of the flow of the polymer liquid. The polymer percentage at the outlet of R-02 was 50%, and the polymer percentage at the outlet of R-03 was 70%. Here, the polymer percentage is a value calculated by the following formula (1). Polymer rate (%) = [(amount of polymer produced) / {(amount of monomer charged)+(amount of solvent)}] × 100 (1) The obtained polymer liquid was heated to 230°C, and then sent to a volatilization tank with a vacuum of 5 torr, where the unreacted monomer and solvent were separated and collected. The reactant was then extracted from the volatilization tank with a gear pump, passed through a die plate to form a strand, and then passed through a water tank to pelletize it, obtaining high impact polystyrene (HIPS). The rubber content of the obtained HIPS was 4.8% by mass. The Mw of HIPS measured under the same conditions as GPPS was 210,000.

[0051] [Preparation of styrene-based thermoplastic elastomer 1] In a reaction vessel, 500.0 kg of cyclohexane and 75.0 g of tetrahydrofuran (THF) were placed, and 1,000 mL of a 10% by mass solution of n-butyllithium in cyclohexane was added as a polymerization initiator solution and kept at 30°C. 20.0 kg of styrene was added to perform anionic polymerization of styrene. At that time, the internal temperature rose to 35°C. After the styrene was completely consumed, 33.4 kg of 1,3-butadiene and 86.6 kg of styrene were added simultaneously, and after the styrene and 1,3-butadiene were completely consumed, the internal temperature of the reaction system was lowered to 75°C, and 60.0 kg of styrene was added all at once to complete the polymerization. Finally, all of the polymerization active terminals were deactivated with water to obtain a polymerization liquid containing a styrene-butadiene copolymer having a polystyrene block and a tapered block of styrene and butadiene. This polymerization liquid was degassed and a pellet-shaped block copolymer was obtained using an extruder. The diene content of the obtained styrene-butadiene copolymer calculated from the amount of monomer charged was 16.7% by mass.

[0052] [Preparation of styrene-based thermoplastic elastomers 2-3] Except for changing the amounts of styrene and butadiene charged, a styrene-butadiene copolymer was obtained in the same manner as in the styrene-based thermoplastic elastomer 1. Table 2 shows the composition and diene amount of each styrene-based thermoplastic elastomer.

[0053] [Table 2]

[0054] [Example 1] Polystyrene resin 1 (GPPS) (20% by mass relative to the total mass of the resin composition), styrene-based thermoplastic elastomer 1 (styrene-butadiene copolymer, diene amount 16.7% by mass) (30% by mass relative to the total mass of the resin composition), and inorganic filler 1 (eggshell powder, average particle size 10 μm) (50% by mass relative to the total mass of the resin composition) were melt-kneaded at 200 ° C., 200 rpm, and discharge of 20 kg / h using a twin-screw extruder (manufactured by Toshiba Machine Co., Ltd., product name "TEM35-B"), extruded into a strand shape, and pelletized. The MFR of the obtained pellets was measured under the following conditions and was 4.8 g / 10 min. In addition, the obtained pellets were molded into a plate with a thickness of 0.40 mm using a heat press (manufactured by Tester Sangyo Co., Ltd., product name "SA-303"), and the tensile modulus of elasticity and tensile elongation at break were evaluated by the following methods. The results are shown in Table 3. The press plate thickness values ​​in Table 3 are values ​​obtained by measuring the thickness of a plate-shaped molded product using a micrometer.

[0055] <mfr> Measurements were performed in accordance with JIS K 7260 at 200°C and a load of 5 kg.

[0056] <Method for measuring tensile modulus> Ten measurement samples were prepared by cutting out the plate-shaped molded product of the resin composition into the shape of a No. 1 dumbbell. Thereafter, the tensile modulus of the measurement samples was measured at a measurement temperature of 23°C, a humidity of 50%, and a pulling speed of 5 mm / min using an autograph (manufactured by Shimadzu Corporation, product name "AGS-X") in accordance with ASTM-D638. The tensile modulus of all the measurement samples was measured, and the average value was evaluated according to the following evaluation criteria. A rating of B or higher was deemed to be acceptable. (Evaluation Criteria) A: Tensile modulus of elasticity is 1,200 MPa or more and less than 1,800 MPa. B: The tensile modulus is 1,000 MPa or more and less than 1,200 MPa, or 1,800 MPa or more and less than 3,000 MPa. C: Tensile modulus of elasticity is less than 1,000 MPa or more than 3,000 MPa.

[0057] <Method of measuring tensile elongation at break> Ten measurement samples were prepared by cutting out a plate-shaped molded product of the resin composition into the shape of a No. 1 dumbbell. The tensile elongation at break of the measurement samples was then measured at a tensile speed of 5 mm / min under conditions of a measurement temperature of 23°C and a humidity of 50% using an autograph (manufactured by Shimadzu Corporation, product name "AGS-X") in accordance with ASTM-D638. The tensile elongation at break of all measurement samples was measured, and the average value was evaluated according to the following evaluation criteria. A rating of B or higher was deemed to be acceptable. (Evaluation Criteria) A: Tensile elongation at break is 10% or more. B: Tensile elongation at break is 5% or more and less than 10%. C: Tensile elongation at break is less than 5%.

[0058] <Evaluation criteria for moldability> The resin composition was molded into an ISO dumbbell shape using an injection molding machine manufactured by Nippon Steel Corporation at a temperature of 200° C. and a mold temperature of 70° C., and the moldability was evaluated according to the following evaluation criteria. A: It can be molded without any problems. B: Those that break at the spool or runner, or those whose molding is soft and flexible.

[0059] [Examples 2 to 7 and Comparative Examples 1 to 4] A resin composition was prepared in the same manner as in Example 1, except that the composition of the resin composition was as shown in Table 3. In addition, pellets were prepared in the same manner as in Example 1, and the MFR was measured. Furthermore, the resin was molded into a plate in the same manner as in Example 1, and the plate thickness, tensile modulus, and tensile elongation at break were measured. The results are shown in Table 3.

[0060] [Table 3]

[0061] As shown in Table 3, the resin compositions of Examples 1 to 7, which satisfy the constitution of the present invention, had good values ​​of tensile modulus and tensile elongation at break even though they contained 50% by mass or more of inorganic filler. In addition, the moldability was also good. On the other hand, the resin compositions of Comparative Examples 1 to 4, which do not satisfy the constitution of the present invention, were inferior in either tensile modulus or tensile elongation at break, and also had poor moldability. From the above results, it was found that the resin composition according to the present invention, which has a low content of styrene-based resin, can provide a molded article having good moldability and excellent tensile modulus and tensile elongation at break.< / mfr>

Claims

1. A resin composition comprising an inorganic filler containing calcium carbonate and a styrene-based resin containing a diene component, The inorganic filler comprises eggshell powder, The content of the inorganic filler is 50% by mass or more based on the total mass of the resin composition, A resin composition having a tensile modulus of 1,000 to 3,000 MPa and a tensile elongation at break of 5% or more, as measured in accordance with ASTM-D638.

2. The resin composition according to claim 1, wherein the eggshell powder has an average particle size of 3 to 50 μm.

3. The resin composition according to claim 1 or 2, wherein the styrene-based resin comprises a polystyrene resin and a styrene-based thermoplastic elastomer.

4. The resin composition according to claim 3 , wherein the polystyrene resin comprises at least one resin selected from general-purpose polystyrene and high-impact polystyrene.

5. The resin composition according to claim 3 or 4, wherein the styrene-based thermoplastic elastomer comprises a styrene-butadiene copolymer.

6. The resin composition according to any one of claims 1 to 5, wherein the content of the diene component relative to the total mass of the resin composition is 3 to 15 mass%.

7. The resin composition according to claim 1 , wherein the resin composition has an MFR (200° C., 5 kg load) of 1.5 g / 10 min or more.

8. The resin composition according to claim 1 , which is for injection molding.

9. A molded article comprising the resin composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • JP1975092342A

  • Modified low-molecular-weight diene polymer

    JP1984199702A

  • High-temperature vibration damper material and vibration damper sheet

    JP1997136998A

  • Styrenic polymer resin pellet

    JP1997267350A

  • Thermoplastic elastomer composition

    JP2003041089A